2016
DOI: 10.1016/j.ajpath.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Channel 4 Encodes a Vascular Permeability Defect and High-Frequency Ca2+ Transients in Severe Pulmonary Arterial Hypertension

Abstract: The canonical transient receptor potential channel 4 (TRPC4) comprises an endothelial storeeoperated Ca 2þ entry channel, and TRPC4 inactivation confers a survival benefit in pulmonary arterial hypertension (PAH). Endothelial Ca 2þ signals mediated by TRPC4 enhance vascular permeability in vitro, but the contribution of TRPC4-dependent Ca 2þ signals to the regulation of endothelial permeability in PAH is poorly understood. We tested the hypothesis that TRPC4 increases vascular permeability and alters the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…However, in the same study, phospholipase Cß (PLCß)-induced Ca 2+ increase was also found to contribute to histamineinduced permeability. Although transient receptor potential canonical 4 (TRPC4) was recently shown to contribute to vascular permeability in a model of pulmonary hypertension in vivo, 199 the finding that stromal interacting molecule 1 (STIM1) decreased barrier function in response to thrombin independent of Ca 2+ entry but rather via direct activation of RhoA 200 suggests that the different signalling pathways may converge on the level of RhoA. In line with this, PKC activation downstream of PLC signalling, which has been shown to reduce VE-cadherin binding and cause intercellular gap formation, 201 is also known to activate RhoA via p115RhoGEF.…”
Section: Roles Of Rhoa and Rac1 In Barrier Destabilizationmentioning
confidence: 99%
“…However, in the same study, phospholipase Cß (PLCß)-induced Ca 2+ increase was also found to contribute to histamineinduced permeability. Although transient receptor potential canonical 4 (TRPC4) was recently shown to contribute to vascular permeability in a model of pulmonary hypertension in vivo, 199 the finding that stromal interacting molecule 1 (STIM1) decreased barrier function in response to thrombin independent of Ca 2+ entry but rather via direct activation of RhoA 200 suggests that the different signalling pathways may converge on the level of RhoA. In line with this, PKC activation downstream of PLC signalling, which has been shown to reduce VE-cadherin binding and cause intercellular gap formation, 201 is also known to activate RhoA via p115RhoGEF.…”
Section: Roles Of Rhoa and Rac1 In Barrier Destabilizationmentioning
confidence: 99%
“…TRPC1/4/5 have been suggested to play multiple roles in various conditions, including epilepsy, fear, pain, severe pulmonary arterial hypertension, vascular inflammation in arthritis, and cardiac remodelling (Figure ). However, the lack of modulators to study the functional roles of these channels have limited progress into their exact role (Alawi et al, ; Camacho Londono et al, ; Francis, Xu, Zhou, & Stevens, ; Minard et al, ; Phelan et al, ; Riccio et al, ; Riccio et al, ; Westlund et al, ; Zheng & Phelan, ). The identification of high‐quality, reliable, selective, and subtype‐specific TRPC1/4/5 pharmacological tools and modulators would perhaps enable a better understanding of TRPC1/4/5 channels in human health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies that have shown the involvement of TRPC channels within the cardiovascular system (Alawi et al, ; Camacho Londono et al, ; Francis et al, ; Lau et al, ; Xiao, Liu, Shen, Cao, & Li, ). Camacho Londono et al () reported that TRPC1 and TRPC4 proteins play a pivotal role in a background Ca 2+ entry pathway, which fine‐tunes Ca 2+ cycling in cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, by measuring calcium signals at high frequency, we found that cytosolic calcium oscillations are superimposed on the global rise in cytosolic calcium. 44 The number of these calcium oscillations expanded greatly in hypertensive pulmonary arteries and they were significantly reduced in pulmonary artery endothelium from TRPC4 KO animals ( Fig. 4b ).…”
Section: Calcium Oscillations and Pulmonary Artery Endothelial Cell Pmentioning
confidence: 89%
“…To address this issue, conduit pulmonary artery segments were isolated from normotensive and hypertensive animals, the endothelium was loaded with the Fluo-4 calcium dye, and calcium transients were measured. 44 Whereas most studies examine endothelial cell cytosolic calcium with low temporal resolution, in these studies, we measured the calcium signal at 9.8 frames/s. This faster resolution enabled measurement of fast calcium oscillations, or transients, which would be missed when measuring at slower time constants.…”
Section: Calcium Oscillations and Pulmonary Artery Endothelial Cell Pmentioning
confidence: 99%